Minireview: 12-Lipoxygenase and Islet β-Cell Dysfunction in Diabetes - Tersey, Sarah A. (Mol Endocrinol, 2015)
The insulin producing islet β-cells have increasingly gained attention for their role in the pathogeneses of virtually all forms of diabetes. Dysfunction, de-differentiation, and/or death of β-cells are pivotal features in the transition from normoglycemia to hyperglycemia in both animal models of metabolic disease and humans. In both type 1 and type 2 diabetes, inflammation appears to be a central cause of β-cell derangements, and molecular pathways that modulate inflammation or the inflammatory response are felt to be prime targets of future diabetes therapy. The lipoxygenases (LOs) represent a class of enzymes that oxygenate cellular polyunsaturated fatty acids to produce inflammatory lipid intermediates that directly and indirectly affect cellular function and survival. The enzyme 12-LO is expressed in all metabolically active tissues, including pancreatic islets, and has received increasing attention for its role in promoting cellular inflammation in the setting of diabetes. Genetic deletion models of 12-LO in mice reveal striking protection from metabolic disease and its complications and an emerging body of literature has implicated its role in human disease. This review focuses on the evidence supporting the proinflammatory role of 12-LO as it relates to islet β-cells, and the potential for 12-LO inhibition as a future avenue for the prevention and treatment of metabolic disease.